2012
DOI: 10.4236/ojpsych.2012.24041
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic density and prevalence of psychiatric morbidity among patients with hiv infection in Sokoto, Nigeria—A control study

Abstract: Background: Previous studies among people living with HIV infection suggested that prevalence of psychiatric morbidity was high. In addition, among non-HIV infected patients, ethnic density influence the prevalence. The present study was aimed to determine the prevalence and effects of ethnic density on psychiatric morbidity among these patients in Sokoto, Nigeria. Methods: This prospective cross-sectional study was conducted among patients who had been diagnosed with HIV infection in a teaching hospital in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…[12]. The finding of the ethnic minorities being more likely to become depressed when compared to the major ethnic group is in keeping with an earlier study in Sokoto, Nigeria [13]. They reported that the major ethnic groups had less rate of depression when compared to the minority ethnic groups.…”
Section: Multivariate Logistic Regressions For the Predictors Ofsupporting
confidence: 83%
See 1 more Smart Citation
“…[12]. The finding of the ethnic minorities being more likely to become depressed when compared to the major ethnic group is in keeping with an earlier study in Sokoto, Nigeria [13]. They reported that the major ethnic groups had less rate of depression when compared to the minority ethnic groups.…”
Section: Multivariate Logistic Regressions For the Predictors Ofsupporting
confidence: 83%
“…Majority of participants that had depression also had a family history of mental illness; this was similar to what was found in a similar study in Nigeria [26]. In another study, it was reported that a family history of depression was quite common among depressed patients with epilepsy [13]. It shows that there is an element of genetic association in those that are vulnerable to depression which may be aggravated by the epilepsy.…”
Section: Factors Associated With Depression In the Patients Withsupporting
confidence: 82%
“…Earlier, the HADS Hausa version was used in a study of depression among Human Immunodeficiency Virus (HIV) / Acquired Immunodeficiency Syndrome (AIDS) outpatients in Aminu Kano Teaching Hospital. 16,17 The instrument was translated into Hausa by an expert in translation, taking cognizance of the semantic and linguistic differences.…”
Section: Introductionmentioning
confidence: 99%